2007
DOI: 10.1016/j.tiv.2007.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the nucleic acid covalent binding capacity of two nitro-substituted benzazolo[3,2-a]quinolinium salts upon enzymatic reduction

Abstract: The DNA binding capacity of two nitro-substituted benzazolo[3,2-a]quinolinium chlorides (NBQs), NBQ-38 and NBQ-95, was evaluated upon their enzymatic reduction with hypoxanthine (HX)/ xanthine oxidase (XO) under anaerobic conditions. In the presence of 2'-deoxyguanosine (2'-dG) or calf thymus DNA, covalent-addition products were monitored. Reactions of each NBQ with 2'-dG or DNA differed in the NBQ to HX molar ratio. Control reactions, one without HX/OX and another under aerobic conditions, were also analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Upon addition of HX/XO to NBQ-91, a broad shoulder builds up with a maximum at 361 nm and another at 400 nm (Figure 2). This observation, together with the evidence for uric acid formation (Figure 3), indicates that NBQ-91 was reduced by HX/XO as previously reported for other nitroquinolinium salts (28, 34). A broad absorption spectrum with two maxima at 365 and 379 nm and a shoulder at 350 nm was observed for BQ-106 in the absence of reducing agent.…”
Section: Resultssupporting
confidence: 88%
“…Upon addition of HX/XO to NBQ-91, a broad shoulder builds up with a maximum at 361 nm and another at 400 nm (Figure 2). This observation, together with the evidence for uric acid formation (Figure 3), indicates that NBQ-91 was reduced by HX/XO as previously reported for other nitroquinolinium salts (28, 34). A broad absorption spectrum with two maxima at 365 and 379 nm and a shoulder at 350 nm was observed for BQ-106 in the absence of reducing agent.…”
Section: Resultssupporting
confidence: 88%
“…The combinations of the evaluated biological activities suggest a nuclear promoted mechanism of cell death. The ability of these compounds especially NBQ 38 to promote DNA alterations also confirms results from previous studies in the formation of 2’-dG-NHBQ 38 adducts in naked DNA were detected [ 12 ].…”
Section: Discussionsupporting
confidence: 86%
“…Both compounds have also shown to be apoptosis inducers [6,7,11]. The formation of C8–2’-dG-BQS adducts with calf thymus DNA under hypoxic environment with NBQ-38, one of the compounds presented in this study, has also been reported [12,13]. …”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Berberine has shown similar activities including anti cancer activity through mitochondria interactions [12]. Our previous work on other compounds from this family of benzazolo[3,2- a ]quinolinium salt (BQS) compounds has demonstrated diverse biological activities such as growth inhibition; apoptosis induction, and DNA adduct formation in cancer types such as epidermoid carcinoma [13-15]. …”
Section: Introductionmentioning
confidence: 99%